1991
DOI: 10.1136/gut.32.8.881
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of adolescents with coeliac disease with a gluten free diet.

Abstract: A cohort of 123 patients with coeliac disease, diagnosed in the first three years of life and followed up for at least 10 years, was reevaluated during the teenage period in terms of compliance with the diet and clinical state. Mucosal structure and lymphocytes were assessed in small intestinal biopsy specimens obtained from 36 subjects, by computerised image analysis. Of these adolescents with coeliac disease, 65% were adhering to a strict gluten free diet, 11*4% were on a gluten free diet but with occasional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
3
12

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 20 publications
9
71
3
12
Order By: Relevance
“…Previous studies have shown that adolescents and those diagnosed with CD by serologic screening are less likely to adhere strictly to a GFD when compared to younger children and adults diagnosed because of classical symptoms [20][21][22][23]. Rates of adherence in adolescent populations vary from 56% to 83% [21,24], while individuals diagnosed with CD at a very young age are reported to have the highest rates of adherence [20]. Furthermore, in a Swedish study, only 36% of adults who were diagnosed with CD at four years of age or older were found to be compliant with the GFD, as compared to 80% of those adults diagnosed prior to their fourth birthday [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that adolescents and those diagnosed with CD by serologic screening are less likely to adhere strictly to a GFD when compared to younger children and adults diagnosed because of classical symptoms [20][21][22][23]. Rates of adherence in adolescent populations vary from 56% to 83% [21,24], while individuals diagnosed with CD at a very young age are reported to have the highest rates of adherence [20]. Furthermore, in a Swedish study, only 36% of adults who were diagnosed with CD at four years of age or older were found to be compliant with the GFD, as compared to 80% of those adults diagnosed prior to their fourth birthday [16].…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with a gluten-free diet is generally supposed not to be very high, with only 17 -65% of coeliac disease patients adhering to a strict gluten-free diet (Kluge et al, 1982;Kumar et al, 1988;Mayer et al, 1991). Allowance of oats can increase compliance to the diet by providing patients with more food alternatives and can also improve the quality of life for coeliac disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Families of children with diabetes and celiac disease should receive nutritional counseling from a registered dietitian who has experience with both diabetes and celiac disease. Gluten-free substitutes are often very high in carbohydrates; additionally, assistance in finding acceptable glutenfree products is essential to maintaining a gluten-free diet (210).…”
Section: Type 1 Diabetes In Children and Adolescentsmentioning
confidence: 99%